Outcomes of fluoroscopy-free retrograde intrarenal surgery and predictive factors of stone-free - ŞEKERCİ, ÇAĞRI AKIN; TANIDIR, YILÖREN (My University, 2021)
OBJECTIVE: To evaluate the outcomes of flouroscopy-free retrograde intrarenal surgery (ffRIRS) and to investigate the factors that may affect stone-free rate. MATERIALS AND METHODS: The charts of patients who underwent ffRIRS between January 2017 and August 2019 were reviewed retrospectively. Patients with missing preoperative imaging and patients with kidney anomalies were excluded from the study. Age, gender, stone size, stone localization, stone density, laterality, operation time, stone-free rate, complications and auxiliary procedures were recorded and analyzed. RESULTS: Study group involved 44 (43.1%) female and 58 (56.8%) male patients. Stone-free rate in a single-session ffRIRS were found to be correlated with stone localization (p = 0.003), stone volume (p = 0.004), and stone density (p = 0.009) but not with age (p = 0.950). Patients with multiple calyceal stones and a stone burden over 520 mm3 were found to be less stone-free. The complication rate in female gender (n = 7) was significantly higher compared to male (n = 1) (p = 0.011). No major complications such as ureteral injury or avulsion were observed. Overall, 13 patients (12.7%) needed auxiliary procedures. The operation time seemed to be affected by stone size and gender (p = 0.005; p = 0.044, respectively). CONCLUSIONS: Stone-free rate in ffRIRS were found to be affected by stone density, size, and localization. Patients with multiple caliceal stones and high stone burden (< 520 mm3) have been found to have low stone-free rate, so one can speculate that having fluoroscopy assistance in RIRS might help us to improve surgical success.
Keywords: Female; Humans; Treatment Outcome; Male; Retrospective Studies; Kidney Calculi; Operative Time; Fluoroscopy